Tindak Ujar Iklan Berbahasa Melayu Manado di Radio - Timboeleng, Donna Retty (Universitas Sam Ratulangi, 2013)
Recently, the development of knowledge is rapidly as language in the advertisement’s aspects. Speech act as a part of pragmatics in language, as two sides of coin, has its development in one side and complication in other side. It occurs in Manadonese Malay radio advertisements as a tool of sharing the ideas. Advertisement in the marketing communication is the reflection of the real condition in community. Therefore, advertisement is related and influenced with the macro environment such as social, economic, politic, language, and culture. Descriptive qualitative is the method used in this research. The advertisements were analyzed based on the content, function, meaning, and mind set. Hereafter, questionnaire and interview were held to find the influence of advertisement in the community, consumer and hearer. The theories used were Austin’s locution, illocution and perlocution. Searle: assertive, directive, comissive, expressive, declarative and Leech’s categories: competitive, convivial, collaborative, and conflictive. Sapir-Whorf’s Hypothesis is used to find the mind set of the speaker. In detecting the influence, the community’s responses were analyzed by using theories of Wardhaugh and Fishman. According to the result of this research and analysis, the data revealed that all the speech act found in the advertisement and the responses were vary. Eventually, conclusion was drawn that all the element of speech act found in the advertisement. The responses were in positive, negative, and neutral. It is strongly suggested to establish a legal institution and the consultant of advertisement production. Extended research is needed in finding the adnertisement’s aspects from the other perspectives of linguistics. Key words: speech act, manadonese malay, radio advertisement.